Sunni Islamic Thought and the Development of Religious Tolerance in North Maluku: Perspective of Sufism and Maslahah - Giling, Mustamin; Thalib, Abdullah; 'Ulama' I , Khaerul Asy'aey; Alhadar, Muhdi; Santalia, Indo (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
Indonesia is home to the world’s largest Sunni Muslim population, where Islam historically developed within the framework of ahl al-sunnah wa al-jamā‘ah, grounded in the creeds of al-Ash‘ari and al-Maturidi, the four Sunni schools of jurisprudence, and classical Sufism. This study examines the role of the Sunni tradition in fostering interfaith tolerance in North Maluku. Employing a qualitative approach, the research draws on field observations, in-depth interviews, and literature analysis, and is analytically informed by Sufi perspectives in Islamic thought and the concept of maṣlaḥah (public welfare) in Islamic law. The findings reveal that the Sunni tradition, particularly through its Sufi teachings, promotes a balanced model of religious moderation that integrates firm theological commitment with social openness. In Indonesia, Sunni Islam has played a significant role in nurturing interfaith tolerance not only at the theological level but also across social, cultural, and political dimensions, both conceptually and in everyday practice. In North Maluku specifically, from the era of the sultanates to the present day, the Sunni tradition has consistently contributed to harmonious interreligious relations, positioning religion as a source of universal compassion. As the majority religious orientation, Sunni Islam advances moderate teachings that encourage peaceful coexistence, as reflected in Sufi ethics and Shafi‘i jurisprudence, which emphasizes the pursuit of social welfare. Consequently, the Aswaja tradition has profoundly shaped Indonesian Islam as an inclusive, humane, and socially responsive religious expression.